TEACHERS' STRATEGY IN INTILLING CHARACTER VALUES IN STUDENTS WITHIN ONLINE LEARNING DURING PANDEMIC (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Problem statement in this current research in that how is the teacher' strategy in intilling character values in students at SDN 03 Kabila, Bone Bolango Regency within online learning during the pandemic? The research aims to find out the corellment of character values in student at SDN 03 Kabila, Bone Bolango Regency. This research is classified as qualitative research where it is conducted through observation, interviews, and documentation. The research findings discover that there are eight-character values instilled by the teachers within online learning, and they include a) responsibility, b) discipline, c) honesty, d) independence, e) creativity, f) tooerance, g) social care , and h) love and peace. In conclusion, the instillment of character values is a pivotal factor in building a good character of the nation's youth so that it must be taught from an early age through elementaru education. Addnomally, the implementation of character education in student should be done through daily habituation and integration with classroom learning activity so that the students can be a better generation in the future